PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO PADA MATA PELAJARAN PKN TERHADAP HASIL BELAJAR SISWA KELAS VII DI MTS NURUL KAROMAH GALIS BANGKALAN - Khairul Anwar; Hefi Rusnita Dewi; M. Sahid (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This study aims to describe student activities, student responses and student learning achievements through the implementation of a portfolio-based learning model. This research is communicative descriptive research. The instruments used in this study were observation sheets of student activities, student response questionnaires and learning achievement test sheets.The results of this study can be described as follows (1) student activities during the teaching and learning process that took place is said to be good, because the average score of observation of student activity is 3.25% (2) students' responses to the implementation of Portfolio-Based learning models are positive because the average score the average of all questionnaires, namely 75.6 (3) student learning achievements are said to be classically completed because as many as 88% of students have finished learning. Overall, it can be concluded from the results of this study that student activities on learning using portfolio-based learning models are in the good category, student responses to learning using portfolio-based learning models are in the positive category, and student learning achievements in learning using portfolio-based learning models said to be classically completed.